The Influence of Digital Marketing, Product Quality, and Price Regarding the Decision to Purchase Chesang Products Banana Fry Bloated - Maulana, Rayhan; Nursanti, Aida; Pratiwi, Dian (International Journal of Economic, Business & Applications, 2025)
This study aims to examine the influence of Digital Marketing,Product Quality, and Price on Purchasing Decisions of Chesang FriedKembung Banana products in Pekanbaru City. The population in thisstudy consists of all consumers/customers who purchased ChesangFried Kembung Banana products. The sampling technique used inthis study is non-probability sampling with purposive samplingmethod, resulting in a sample of 110 consumers. The data analysismethod used is multiple linear regression analysis using SPSSVersion 26 software. The results show that there is a positive andsignificant influence between Digital Marketing on PurchasingDecisions. There is a positive and significant influence betweenProduct Quality on Purchasing Decisions. There is a negative andsignificant influence between Price on Purchasing Decisions. Thereis a positive and significant simultaneous influence between DigitalMarketing, Product Quality, and Price on Purchasing Decisions